ANALISIS KINERJA SIMPANG BERSINYAL WARUNG JAMBU MENGGUNAKAN PTV VISSIM - Choirul Ichwan; M. Pahrial (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2026)
The significant growth in the number of vehicles in Bogor City causes high traffic loads at the Warung Jambu intersection, thus affecting the performance of the intersection and causing quite high delays. This research aims to analyze the performance of the Warung Jambu signalized intersection using PTV Vissim microscopic simulation software. The data used includes traffic volume, geometric conditions of intersections, signal cycles, and vehicle speeds obtained through field surveys on weekdays and weekends. The research results show that the level of service (LOS) of the intersection is in categories E to F, indicating congested to very bad conditions. The average delay on weekday mornings reached 59.11 seconds (LOS E), while on weekends it increased significantly with a value of 70.95 seconds (LOS F) on Sunday afternoons. Modeling also shows that the maximum queue length can reach more than 500 meters at some intersection arms. This condition indicates the need for a comprehensive evaluation of signal arrangements and traffic management at the Warung Jambu intersection area.